Use of Nonsteroidal Anti-Inflammatory Drugs among Healthy People and Specific Cerebrovascular Safety. Issue 7 (October 2014) - Fosbøl, Emil L.; Olsen, Anne-Marie Schjerning; Olesen, Jonas Bjerring; Andersson, Charlotte; Kober, Lars; Torp-Pedersen, Christian; Gislason, Gunnar H.
Background: Nonsteroidal anti-inflammatory drugs can increase bleeding and thrombosis, but little is known about the cerebrovascular safety of these drugs, especially among healthy people. Aims: The aim of this study was to examine the risk of ischemic and hemorrhagic stroke associated with the use of nonsteroidal anti-inflammatory drugs in healthy people. Methods By individual-level linkage of nationwide administrative registers in Denmark, information on hospital admissions, prescription claims, vital status, and cause of death were obtained. A cohort of healthy people without hospital admissions for five-years and no important prescription claims for two-years was selected. Case crossover and Cox proportional hazard models were used to analyze the relationship between nonsteroidal anti-inflammatory drug utilization and specific cerebrovascular risk (fatal or non-fatal ischemic or hemorrhagic stroke). Results: We selected 1 028 437 healthy individuals (median age 39 years). At least one nonsteroidal anti-inflammatory drug was claimed by 44·7% of the study population, and the drugs were generally used for a short period of time and in low doses. High-dose ibuprofen and diclofenac were associated with increased risk of ischemic stroke [hazard ratio 2·15 (95% confidence interval 1·66–2·79) and 2·37 (confidence interval 1·99–2·81), respectively]. Diclofenac was also associated with increased risk of hemorrhagic stroke and so was naproxen [hazard ratio 2·15 (confidence interval 1·35–3·42)]. Conclusions In healthy individuals, use of commonly available nonsteroidal anti-inflammatory drugs such as ibuprofen, diclofenac, and naproxen was associated with increased risk of stroke.